Unveiling childfree voices: representation, humor, and resistance on Instagram - Esra Bozkanat (methaodos.revista de ciencias sociales)
This research aims to reveal the social representation of voluntary childlessness (VC) on Instagram, focusing on how individuals construct and defend their childfree identity in a digital visual environment. Grounded in Social Representations Theory (SRT), the analysis examines 212 posts from Instagram accounts dedicated to VC content. Using netnography—a qualitative method for studying online communities—and thematic analysis, recurring patterns in how VC is communicated and negotiated are explored. Posts were selected based on relevant hashtags (e.g., #childfreebychoice) and representation-focused content, excluding promotional or antinatalist material. The analysis identifies three key mechanisms of representation: anchoring (e.g., the use of terms like “childfree” instead of “childless”), objectification (e.g., memes that visualize social stigmas), and repudiation (e.g., direct responses to common stigmas such as regret or selfishness). Findings demonstrate how Instagram functions as a space for identity performance, defensive communication, and resistance to dominant pronatalist narratives. This research contributes to digital representation scholarship by showing how platform affordances and user-generated content reshape marginalized social identities and offers practical implications for understanding how visual media enables counter-narratives that challenge traditional norms around parenthood.